Application of an Electronic Aroma Sensing System to Cork Stopper Quality Control - Rocha, S; Delgadillo, I; Ferrer Correia, A J; Barros, A; Wells, P (Journal of Agricultural and Food Chemistry, 1998)
Cork odors were characterized using an electronic aroma sensing system. The electronic system is a compact, benchtop instrument comprising a sensor array, signal processing hardware, a measurement algorithm, and a pattern classification system. The sensor array responds to the presence of aroma volatile compounds by changes in their electrical properties. Resistance changes are displayed as a histogram, which is a fingerprint of the aroma being analyzed. Five different cork odors were studied: NE, which is considered as standard cork odor; CO, exhibiting the pleasant boiled cork odor (it is also considered as a good odor); PO, corresponding to rotten odor; and B and BO, representing moldy and very intensely moldy odors, respectively. This electronic aroma sensing system could discriminate quickly and objectively between acceptable odor and the unacceptable taint. Characterization and selection of a subset of sensors were performed. A relation between sensors and specific odors was established. The system, once trained with representative acceptable and unacceptable samples, could be used as a simple quality control tool and incorporated into the normal quality control procedures for each batch of product, by providing real-time analysis of a sample overall aroma.
doi: 10.1021/jf970259+
Keywords: Cork stoppers; electronic aroma sensing system; off-flavors; quality control; “standard” aroma